Omega-3 Fatty Acids as Supplements and Cryoprotectants and Positive Outcomes for Human Seminal Cryopreservation: A Study in the Iraqi Context - Al-Obeidy, Mustafa; Akkila, Sameh; Noel, Khalida (Jordan Medical Journal, 2023)
Background: With the increasing deterioration in male fertility rates over the past few decades, assisted reproductive therapy via sperm banking has gained considerable attention from different health authorities worldwide. The process of sperm cryopreservation exerts certain harmful effects on sperm quality parameters. The aim of the current study was to examine the effect of omega-3 on human sperm cryopreservation as a dietary supplement and as a cryoprotectant stimulant. Methods: From healthy men, 120 seminal fluid samples were randomly collected for cryopreservation (for 30 days). All samples were divided into three groups (40 in each). The supplement group (SG) (first group) had been given dietary supplements of omega-3 (30% EPA: 20% DHA) for eight weeks before sample collection. The samples of the cryoprotectant group (CG) (second group) were treated with omega-3 additive in the diluent at the time of being collected and before we cryopreserved them. The samples from the control group (third group) were cryopreserved without any dietary or cryoprotectant supplementation. Initial seminal analysis was recorded and post-thawing assessment of sperm motility, vitality (using eosin test) and oxidative stress (using a nitro blue tetrazolium (NBT) test) were compared. Results and Conclusion: SG samples had greater initial seminal fluid volumes, as well as better sperm motility and vitality, but the oxidative stress assessment did not differ significantly pre-cryo. Post-thawing assessment revealed that the CG group had the best parameters of motility, vitality and oxidative stress. These results may be related to the positive effects of omega-3 fatty acids on reproductive glands, hormonal milieu, sperm function and structure, making it a suitable biostimulant for improving the outcome of human sperm banking. Results were comparable to multiple previous animal studies.